Proceedings from the ECFIN workshop "The budgery implications of structural reforms " Brussels, 2 December 2005 - The budgery implications of structural reforms 2005 : Brussels, Belgium); Deroose, Servaas; Flores, Elena; Turrini, Alessandro 1966-; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium : European Comission: Directorate-General for Economic and Financial Affairs, 2006)
Most of the reforms discussed within the framework of the Lisbon strategy will benefit public finances in the long term. However, in the short-term, there could a trade-off between some structural reforms and budgetary discipline. This possible tension between reforms and fiscal discipline was identified by academic economists as a possible drawback of the Stability and Growth Pact since its inception.... The analytical approaches differ across the papers, as well as the datasets employed. This poses an issue in deriving across-the-board conclusions. Nevertheless, a tentative summary of the main common findings can be made as follows. First, many reforms imply considerable potential longterm gains for public finances. However, the size of the impact depends crucially on the design of the reform and the overall economic environment. Second, although the existence of short-term costs of long-term beneficial reforms cannot be easily dismissed, the magnitude of the short-term budgetary impact varies considerably depending not only on which sector of the economy is reformed (e.g., labour market reforms versus pension reforms) but also on the specific design of the reform (e.g., parametric pension reforms versus systemic reforms introducing mandatory funded schemes recorded outside government). Third, the impact of the budgetary situation and the fiscal stance on the likelihood of structural reforms is not clear-cut. The evidence seems consistent with a possible trade-off between fiscal consolidation and labour market reforms, but such trade off is not visible for other type of reforms (product market reforms, financial market reforms, pension reforms).
Economic Papers.